ENGLISH TEACHERS’ PERCEPTION ON THE IMPACT OF PRE AND IN-SERVICE TRAINING - Nur Laily Lupita Sari; Risvi Uli Rosyidah; Evi Yuniarisda Hutagalung (Universitas Teknokrat Indonesia, 2022)
Numerous efforts have been undertaken by not only government but also other institutions in order to reach the goal of enhancing teacher professionalism. Pre-service and in-service trainings are the examples. However, there is actually a need to see teacher’s perception towards the effects on joining such trainings and see what issues emerge related to the trainings. This paper attempts to answer all these needs by giving the results of interview with vice principal of curriculum, English teachers, and students of SMKN 3 Malang. This research employs narrative inquiry research. The research uses interview to collect data from the vice principal of curriculum, three English teachers, and students who are taught by the teachers. The results showed that pre-service and in-service training give positive impacts on the professional development of the teachers at SMKN 3 Malang. Issues related to the trainings appear into some forms. Teachers’ unpreparedness in teaching vocational school students due to the lack of trainings about ESP that should have been actually taught more at university. Therefore, it is apparently important for government or universities to provide more pre-service trainings for student-teachers, not only about teaching general English, but also English for special purposes. The researchers also perceive that it is not exaggerating for vocational schools to give more trainings on ESP for the teachers before they are hired. Also, the teachers worry about the correct format of recent curriculum and lesson plan taught on some in-service trainings.